ChemInform Abstract: Regiospecific Synthesis of Dithiocarbamates via Markovnikov Addition Reaction. Issue 38 (30th August 2013) - Halimehjani, Azim Ziyaei; Zanussi, Hamed Pasha; Ranjbari, Mohammad Amin
Abstract N‐Vinylpyrrolidine reacts with dithiocarbamic acids, generated in situ, to give the target compounds as Markovnikov products.